Perceptions of Teachers on the Implementation of the Competence-Based Curriculum in Secondary Schools in Bundibugyo and Ntoroko Districts, Uganda - Namubiru, Aisha; Kisembo, Maliko; Kasiita, Tawheed; Kagambe, Edmond; Kasiita, Tawfik (East African Journal of Education Studies, 2024)
The Competence-Based Curriculum (CBC), introduced to enhance learners' skills and competencies, has undergone nationwide adoption, prompting the need to assess its effectiveness at the grassroots level. This study delves into the perceptions of teachers regarding CBC implementation in secondary schools within the Bundibugyo and Ntoroko Districts. Employing a mixed methods approach through descriptive survey research, data was collected via interviews, group discussions, and questionnaires. The study's sample size comprised 397 participants, including 365 teachers selected via simple random sampling and 32 purposefully selected school administrators from twenty-one secondary schools in the target districts. Study findings indicate diverse perspectives among teachers regarding the CBC's implementation, highlighting positive aspects like enhanced skill development and learner-centred approaches, alongside challenges such as resource constraints, limited training, and varied levels of preparedness among educators. Notably, teachers expressed an overall negative attitude toward the lower secondary school CBC implementation. The study reveals a variety of perspectives among teachers regarding the implementation of the CBC. Positive aspects include the emphasis on skill development, learner-centred approaches, and the potential to provide real-world applications. However, challenges such as inadequate resources, limited training, and varying levels of preparedness and attitude among educators are identified as potential hindrances to the successful implementation of the curriculum. Notably, teachers expressed an overall negative attitude toward the lower secondary school CBC. The findings have implications for educational policymakers, curriculum developers, and school administrators seeking to refine the implementation strategies and address the challenges faced by teachers in delivering the Competence-Based Curriculum. The study recommends initiatives such as professional development and training for teachers, adequate supply of instructional materials, strategic teacher recruitment, and the establishment of peer learning networks. Furthermore, involving various stakeholders like parents, community leaders, and local authorities is crucial for fostering a supportive ecosystem conducive to effective CBC delivery